Diseño de la Infraestructura Eléctrica y Neumática para la Serviteca Club Services la 28 S.A.S (2022)
The special transport company FSG Located in the city of Bogotá, it has a fleet of approximately 500 vehicles, mainly PICK UP trucks. Observing the growth and projection of the vehicle fleet of this company located in the city of Bogotá, taking into account that automobiles, when providing different services, require inspection, maintenance and correction of faults to guarantee the proper functioning of the vehicle as the main element based on the company, in order to avoid accidents and prolong the useful life of the machines, considering the direct costs, delay times and sometimes poor quality of the service that these maintenance require, the transport company decides that it requires a service center or repair shop automotive technical service. For this, it has a property in the town of Barrios Unidos, for the new Serviteca called CLUB SERVICES LA 28 S.A.S. For this purpose, it is important to choose the machinery to be operated, taking into account the existing regulations for electrical systems and tires required in this activity. The purpose of this project is the development of electrical and pneumatic designs considering the calculations that govern these sciences whose primary purpose is to provide the operation and safety in this work.